2002
DOI: 10.1207/s15327744joce1203_01
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Telemedicine Technology by Health Care Organizations: An Exploratory Study

Abstract: Recent advances in information and biomedicine technology have significantly increased the technical feasibility, clinical viability, and economic affordability of telemedicine-enabled service collaboration and delivery. Health care organizations around the world have become increasingly interested in acquiring and implementing telemedicine technology to improve or extend existing patient care and services. The ultimate success of telemedicine in an adopting organization requires adequate attention to both tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(71 citation statements)
references
References 45 publications
7
64
0
Order By: Relevance
“…A vendor is assigned to do the network-based application to integrate in different hospital areas such as wards, pharmacy, reception, financial and departments. In addition, they found that the vendors are far from them and updating their system assuming their needs takes sometimes, hence HIS implementation has been unsuccessful [22], [132]. Chang et al [87] noted that in Taiwan, healthcare technology assisted by vendors usually provides solutions from on-site training to link the innovative technology to the IS buyers.…”
Section: Vendor Supportmentioning
confidence: 99%
“…A vendor is assigned to do the network-based application to integrate in different hospital areas such as wards, pharmacy, reception, financial and departments. In addition, they found that the vendors are far from them and updating their system assuming their needs takes sometimes, hence HIS implementation has been unsuccessful [22], [132]. Chang et al [87] noted that in Taiwan, healthcare technology assisted by vendors usually provides solutions from on-site training to link the innovative technology to the IS buyers.…”
Section: Vendor Supportmentioning
confidence: 99%
“…Reliability is considered a factor of system quality and satisfaction in information and telemedicine systems [67,68].…”
Section: Reliabilitymentioning
confidence: 99%
“…The acceptance or assessment of telemedicine technology by a physician understandably may be time-variant, adjusted, or modified as the physician gains additional knowledge about or experience with the technology. In effect, results from prior research (such as [25,47]) have suggested that the relative influence of key technology acceptance factors may change as users become more experienced with the technology. Hence, our findings and discussion indeed represent a snapshot of the technology acceptance phenomenon of interest Downloaded by [University of Sussex Library] at 10:47 06 February 2015 and their generalization requires cautious interpretation.…”
Section: Significance Of Perceived Technology Controlmentioning
confidence: 99%